Visual Computing Lab 30 anni di graf ica 3D in Italia - Scopigno, Roberto; Montani, Claudio (Archeomatica, 2015)
The Visual Computing Lab of CNR-ISTI (an Institute of the Italian national Research Council) is active on several computer graphics topics, including 3D acquisition, sampled 3D data processing, geometry processing, efficient visualization, web- and mobile-based 3D data presentation, RTI images, 3D printing. The main application domains are nowadays the Cultural Heritage and Digital Humanities sectors. The Visual Computing Lab has a very solid international visibility, gained by means of an excellent scientific production and the work done by designing and maintaining open source resources. We are also serving the community by organizing scientific events, conferences, summer schools and contributing to the management of international journals. Awards have been assigned to several Visual Computing Lab members (P. Cignoni, R. Scopigno, M. Tarini). We have a solid experience with EC projects and collaborations with a number of CH institutions in Italy and abroad.